A three-step approach for co-locating nature-based solutions within offshore wind farms - Rendle, Emma Jane; Hunt, Emily Louise; Bicknell, Anthony William James (Frontiers in Ecology and Evolution, 2023)
The extent of seabed licensed for offshore renewables is being expanded with the global requirement to reduce carbon emissions. The opportunity for Nature-based Solutions for restoration, conservation, mariculture, infrastructure protection, and carbon sequestration initiatives are being explored internationally. Co-location of marine renewable or structures with conservation initiatives offers the opportunity to support populations of threatened species and contribute to wider ecosystem services and benefits. Building on experience from a North Sea project, we explore the feasibility to co-locate bivalve species at offshore wind farms. We present a three-step approach to identify offshore wind farm sites with the potential to co-locate with compatible species within a marine licensed area, based on environmental and physical conditions and biological tolerances. These steps are, 1) information collection and data synthesis, 2) data analysis through site suitability and species compatibility assessments, and 3) numerical modelling approaches to test the feasibility of pilot studies and scale-up planned operations. This approach supports feasibility assessment by identification of sites where Nature-based Solution project success is more likely or certain, thereby reducing project costs and risk of failure. An example case study is provided using Gunfleet Sands offshore wind farm (southeast England) and the restoration and conservation of the commercially valuable European Flat Oyster (Ostrea edulis).